The impact of nutritional FoPL on Slovak consumer behavior: Insights from online Eye Tracking and FaceReader analysis - Rusková, Adriana; Berčík, Jakub; Tkáč, Filip; Neomániová, Katarína (Italian Journal of Food Science, 2025)
Promoting a healthy lifestyle is a primary objective for governments and the food sector, targeting increasing obesity rates through efficacious interventions. One method involves employing Front-of-Pack Labeling (FoPL) to convey explicit nutritional information. The primary objective of this study was to examine consumer reactions to determine their views toward clear information on FoPL, evaluating the effects both explicitly and implicitly through eye-tracking and face-reading technologies. A survey evaluated preferences for cereals, yoghurt, and protein bars, evaluating visual attention and emotional responses before and after the introduction of two types of FoPLs. The study concludes that nutritional labeling can effectively promote healthier eating habits, especially for cereals and protein bars.